Highlights on recent books | أضواء على كتب حديثة - Aatama | عتمة, Walid Nadir | وليد نذير (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
King Fahd National Library acquires ancient and modern Saudi literature published inside and outside the Kingdom. It prepares indexes, indexes, bibliographic works, guides, authority lists, and everything related to translations of notable figures and verification of personal information that is related to documenting national intellectual production. | تقتني مكتبة الملك فهد الوطنية المؤلفات السعودية القديمة والحديثة المنشورة داخل المملكة وخارجها. وَتُعِدُ الفهارس والكشافات والأعمال الببليوجرافية والأدلة والقوائم الاستنادية، وكل ما له صلةبتراجم الأعلام والتحقق من المعلومات الشخصية التي ترتبط بتوثيق الإنتاج الفكري الوطني.